List of species and vegetal communities of Isla Grosa (Murcia, España) - Esteve Chueca, Fernando; Esteve Raventós, Fernando (Lazaroa, 1988)
The vegetal population of Isla Grosa, island located in the neighbourhood of Mar Menos (Mediterranean Sea), is studies. It is registered the presence of the association Mayteno-Periplocetum. Likewise a registrer of other species is given, being this the first vegetal contribution to this volcanic island.